Islam Fobi dan Aksi-aksi Radikal - Iskandar, Mohammad (UI Scholars Hub, 2010)
During the Dutch colonial government, social protests under the leadership of some Islamic ulamas were suppressed ruthlessly. In 1710, during the time of the East India Company (VOC), some farmers from Jampang, Sukabumi led by two ulamas rebelled against the Company. Even after the Diponegoro war in Java in 1883, in 1885-1888 there were farmers fighting against the colonial government in Ciomas, Banten and the war was named a holy war, fi sabililah war, and so were in 1904 in Aceh and in 1919 in Cimareme, Garut. Since Islamophobia became a modern phenomenon, and it did not only happen in recent occurrence of the post World Trade Center tragedy, it has been taken place even in the past. The general colonial policy was cautious against Islam and it barred the growth of pesantren, or the religious schools, and marginalized them for its anti-modernist stand. Indonesia, the United States, the United Kingdom, and Australia indirectly labeled Islam as terrorists.